LAPORAN KASUS: NEONATAL DENGUE - I Gusti Ngurah Alit Hendra Wahyudi; Gusti Ayu Nyoman Yulia Sitta Dewi (Mandala Of Health, 2022)
Background : Dengue fever in late pregnancy puts the fetus at great risk because fewer maternal-specific antibodies cross the placenta, leading to a high probability of neonatal dengue infection. We followed a patient in the pediatric health department of the Bali Mandara Hospital. Case Persentation : A 9-day-old baby boy complained of fever for 3 days up to a temperature of 39℃; the fever rose up and fell, but the fever did not go down to normal temperature. On physical examination, the baby was found to be less active, crying enough, suction reflex (+), pulse 135x/minute, breathing: 44 x/minute, temperature: 38.8 (axillary), SpO2: 93%, jaundice (+), lower extremities: warm acral (+), left petechiae (+), CRT <2'', jaundice skin of Kramer 2-3. Laboratory test result’s showed the platelets (69.000), hematocrit(52.2), positive dengue NS1 antigen, and positive dengue IgG and IgM. The patient was diagnosed with neonatal dengue and admitted to Perinatology. Optimal management is needed to treat neonatal dengue. Conclussion : It is Importance to know the transmission of dengue infection to infants, especially in endemic areas. Considering the complication that may occur, early recognition of dengue will significantly reduce infant mortality. Careful monitoring and proper laboratory tests can lead to a smooth recovery.